Pilot-scale mechanical production of cellulose nanofibrils: Energy-structure trade-offs during disc refining - Dawood Bin Fazal; Gil Garnier; Warren Batchelor (Carbohydrate Polymers, 2026)

Techno-economic evaluation of multiple product scenarios from pineapple leaf waste in integrated biorefinery - Poornima Vengaprath Bhattathiri; Warren Batchelor; Antonio Patti; Amit Arora (Bioresource Technology Reports, 2025)

Enhanced analysis of cellulose nanofibril film structure - Hans Estrella Cainglet; D. Mark Martinez; James Drummond; Samuel N.M. Brown; Gil Garnier; Joanne Tanner; Warren Batchelor (Carbohydrate Polymers, 2025)

Legume protein gelation: The mechanism behind the formation of homogeneous and fractal gels - Alice Y.J. Tiong; Simon Crawford; Liliana de Campo; Vasyl Ryukhtin; Christopher J. Garvey; Warren Batchelor; Leonie van ’t Hag (Food Hydrocolloids, 2025)

Cellulose nanofibre films as a substitute for plastic packaging: A comparative environmental life cycle assessment - Humayun Nadeem; Philippe Nimmegeers; Warren Batchelor; Pieter Billen (Food and Bioproducts Processing, 2024)

Pea and soy protein isolate fractal gels: The role of protein composition, structure and solubility on their gelation behaviour - Alice Y.J. Tiong; Simon Crawford; Nykola C. Jones; Gareth H. McKinley; Warren Batchelor; Leonie van ’t Hag (Food Structure, 2024)

Sustainable production of nanocellulose: Technoeconomic assessment, energy savings and scalability - Wriju Kargupta; Thomas Stevenson; Scot Sharman; Joanne Tanner; Warren Batchelor (Journal of Cleaner Production, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Trade‐off Between Environmental Impacts in Water Recycling Systems Using Industrial Effluent - Matthew O'Connor; Gil Garnier; Warren Batchelor (Journal of Industrial Ecology, 2014)
Summary A life cycle assessment was conducted on three industrial effluent water recycling options using a one‐, two‐, and three‐stage effluent treatment plant composed of clarification, aerobic treatment, and ultrafiltration processes. The impact categories dominated by energy use and the category of freshwater use were then further investigated and compared between each recycling system. A dual functional unit of recycled water delivered and effluent treated was identified to make the recycling options functionally equivalent. Three‐stage water recycling was the environmentally preferred option, with all three water recycling options investigated producing similar environmental impacts in most impact categories, with the exception of freshwater use, where the one‐ and two‐stage treatment options performed significantly worse than the three‐stage treatment. It was found that the impact categories of global warming potential and nonrenewable energy demand did not directly correlate with each other as a result of direct greenhouse gas emissions from sludge disposal. The construction of the equivalent systems shows that external systems required for functional equivalence are important in water recycling comparisons, and considering dual functional units is important for comparing water recycling options. With the increasing prevalence of industries utilizing biomass and other renewable fuels, it is becoming more apparent that measuring energy usage is not sufficient, and the specific impacts and damages associated with energy consumption need to be evaluated. This study provides a framework to identify opportunities in industrial wastewater management, which can be particularly important in industries with large effluent flows and high organic loadings.

Life Cycle Assessment of Advanced Industrial Wastewater Treatment Within an Urban Environment - Matthew O'Connor; Gil Garnier; Warren Batchelor (Journal of Industrial Ecology, 2013)
Summary A dissolved air flotation (DAF) system upgrade was proposed for an urban paper mill to recycle effluent. To understand the influence of operating variables on the environmental impacts of greenhouse gas (GHG) emissions and water consumption, a dynamic supply chain model was linked with life cycle assessment (LCA) to produce an environmental inventory. Water is a critical natural resource, and understanding the environmental impacts of recycling water is paramount in continued development of sustainable supply chains involving water. The methodology used in this study bridged the gap between detailed process models and static LCA modeling so that operating variables beyond discrete scenario analysis could be investigated without creating unnecessarily complex models. The model performed well in evaluating environmental impacts. It was found that there was no single optimum operating regime for all environmental impacts. For a mill discharging 80 cubic meters of effluent per hour (m 3 /hour), GHGs could be minimized with a DAF capacity of 17.5 m 3 /hour, while water consumption could be minimized with a DAF capacity of 25 m 3 /hour, which allowed insight into where environmental trade‐offs would occur. The study shows that more complexity can be achieved in supply chain modeling without requiring a full technical model. It also illustrates the need to consider multiple environmental impacts and highlights the trade‐off of GHG emissions with water consumption in water recycling. The supply chain model used in this water treatment case study was able to identify the environmental trade‐offs from the operating variables selected.